2004
DOI: 10.1039/b314548d
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the long-term thermal stability of particulate and monolithic poly(styrene-divinylbenzene) capillaries in reversed-phase liquid chromatography

Abstract: In the present study, the long-term high-temperature (>80 degrees C) and temperature programming stability of fused silica capillaries packed with 5 microm PLRP-S 300 A and monolithic PS-DVB capillaries (both 180 microm id x 6 cm) under reversed-phase conditions has been examined. In isothermal mode, the columns were defined as temperature-stable when a less than 10% change in apparent retention factors (k) and a less than 20% change in "retention time/peak width"-factors (n) of the probe solutes (proteins) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…To date, and despite the enormous significance for users, only a few studies related to the stability and repeatability of monolithic columns are found in the literature [18,25,26]. The most comprehensive study was published in 2002 by Kele and Guiochon [27].…”
Section: Introductionmentioning
confidence: 99%
“…To date, and despite the enormous significance for users, only a few studies related to the stability and repeatability of monolithic columns are found in the literature [18,25,26]. The most comprehensive study was published in 2002 by Kele and Guiochon [27].…”
Section: Introductionmentioning
confidence: 99%
“…2 for the first time. This also represents a significant improvement on previous work using polymer monoliths with hydroorganic eluent which used a maximum temperature of only 140 C. 12 The long term stability of the capillary columns used in this study was investigated by subjecting the column to approximately 1000 column volumes ($30 hours) of continuous operation at 220 C. Comparison of chromatograms obtained before and after the 1000 column volumes of continuous operation (Fig. 2) highlights the stability and maintained performance of the column under high temperature conditions.…”
mentioning
confidence: 82%